Role of intergenerational workforce in the relationship between organizational justice and organizational identification in selected merger and acquisition (M&A) organizations - Umar Baki, Nordahlia; Ismail, Maimunah; Abu Samah, Bahaman; Omar, Zoharah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Merger and acquisition (M&A) nowadays become a trend after the beginning of world economic crisis in 1996 to 1997. Many organizations decided to have M&A in order to survive during the fast pace economic environment. This study focuses on how three types of organizational justice (distributive, procedural and interactional justice) contribute to organizational identification of employees after an M&A deal. Most of the studies on M&A were based on financial aspects and very little investigation focused on the human side of M&A such as perception on organizational identification and how does organizational justice contribute to organizational identification. Hence, this study explored the influences of organizational justice dimensions on organizational identification with intergenerational workforce as a moderator. This study uses Social Identity Theory as its theoretical foundation. This study has been conducted in selected organizations in public and private sector that have undergone M&A in the past five years. A total of 219 respondents involved in this study and the data were analyzed using Structured Equation Modeling. An explanatory power of 28% explained variances in organizational identification by the organizational justice dimensions. This result further revealed that the intergenerational workforce significantly moderated the relationships between distributive justice and interactional justice with organizational identification. Implications to HRD in Malaysia are discussed.